Mental health treatment among older adults with mental illness on parole or probation - William C. Bryson; Brandi P. Cotton; Lisa C. Barry; Martha L. Bruce; Jennifer Piel; Stephen M. Thielke; Brie A. Williams (BMC, 2019)
Abstract Background The number of older adults on parole and probation is growing at an unprecedented rate, yet little is known about the mental health needs and treatment utilization patterns among this group. The objective of this study is to compare the prevalence of serious or moderate mental illness (SMMI), and the proportion of those with SMMI who receive mental health treatment, among community-dwelling older adults on correctional supervision (parole or probation) vs. not on correctional supervision. Methods Design: Cross-sectional analysis of data from the 2008-2014 National Surveys for Drug Use and Health (NSDUH). Setting: Population-based national survey data. Participants: Older adults (age ≥ 50) who participated in the NSDUH between 2008 and 2014 (n = 44,624). Participants were categorized according to whether they were on parole or probation during the 12 months prior to survey completion (n = 379) vs. not (n = 44,245). Measurements: Probable SMMI was defined using a validated measure in the NSDUH. Mental health treatment included any outpatient mental health services or prescriptions over the 12 months prior to survey completion. We compared the prevalence of SMMI, and the proportion of those with SMMI who received any treatment, by correctional status. Results Overall, 7% (N = 3266) of participants had SMMI; the prevalence was disproportionately higher among those on parole or probation (21% vs. 7%, p <  0.001). Sixty-two percent of those with SMMI received any mental health treatment, including 81% of those on parole or probation and 61% of those who were not (p <  0.001). This result remained statistically significant after logistic regression accounted for differences in sociodemographics and health. Conclusions SMMI is disproportionally prevalent among older adults on parole or probation, and community correctional supervision programs may be facilitating linkages to needed community-based mental health treatment.